Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - Ted McCadden; Robin Redmon Wright (Adult Education Research Conference, 2018)
Using the theoretical frameworks of embodied learning and gender performativity, we examine the narratives of nine other-than-heterosexual adult male actors for their experiences of gender identity development through theatre performance.
Keywords: embodied learning; gender performativity; adult development